Relational spaces: wit(h)ness-ing in writescapes. Issue 4 (3rd July 2020) - Koro-Ljungberg, Mirka; Löytönen, Teija; Wells, Timothy
ABSTRACT: This paper might not describe spatial writing or qualitative inquiry. This paper might not express or represent writing in well-defined space by clearly identified scholars or authors. This paper might not write and presented images might not speak. Instead, possibilities in this paper might be stimulated through the acts of reading, writing, thinking, and doing. Writescapes, as lived and discussed in this paper, have potential to create and produce other writings, becoming thinkings, and conceptual experimenting in relation to qualitative inquiry even at the times of continuously changing political apparatuses. As such writescapes produce often in very unexpected ways through their relationality and connectedness and they bring together writers, texts, spaces, and processes. In this article, we interact with spatialized texts and relational processes in very intimate ways acknowledging our scholarly and socio-political contexts but at the same time working against normative scholarship and linear scholarly thinking and writing.